Prosthodontic care and management of patients with MRONJ from different microbiological backgrounds - Flóra Alíz Lakatos; László Kádár; Péter Schmidt; János König; Andrea Bródy; Károly Frigyes Mensch (Hungarian Dental Association, 2024)
Medication-related osteonecrosis of the Jaw (MRONJ) is a severe condition of multifactorial origin, with its exact etiological factors still not fully understood. Besides bisphosphonates, many other drugs are responsible for the development of this condition. The etiology of MRONJ is not precisely known, but infectious origins are being attributed to greater significance. Recently, several authors have highlighted the potential role of Actinomyces strains in the disease course. This publication presents the prosthetic rehabilitation of two MRONJ patients with different microbiological backgrounds and thus different treatments. One patient received solely surgical therapy, while the other underwent both surgical and long-term conservative treatment, resulting in recovery for both. Both patients regularly attend follow-up appointments, show no signs of MRONJ recurrence, and are satisfied with their dental prostheses both functionally and aesthetically.